2022
DOI: 10.3389/fendo.2022.889845
|View full text |Cite
|
Sign up to set email alerts
|

Global Research Trends on Infertility and Psychology From the Past Two Decades: A Bibliometric and Visualized Study

Abstract: ObjectivesThe aim of this study was to evaluate the global scientific output of research on infertility and psychology; explore the current status and trends in this field through the cooperation of authors, countries, and institutions; shed light on the direction of clinical infertility research in the future, and provide inspiration for targeted diagnosis and treatment of infertility.MethodsResearch publications on infertility and psychology from the past two decades were retrieved from the Web of Science Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 103 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have shown that besides being unable to conceive naturally, infertility is also related to various physical and mental diseases such as anxiety, depression, obsessive-compulsive symptoms and sleep disorder [ 8 , 9 ]. In the past years, infertility was considered as a shameful disease, and society and family might give individuals and couples a greater psychological burden which greatly affected the physical and mental health of infertile patients [ 10 ]. For infertile patients, first went to outpatient consultation or chose assisted reproductive technology treatment might cause anxiety [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that besides being unable to conceive naturally, infertility is also related to various physical and mental diseases such as anxiety, depression, obsessive-compulsive symptoms and sleep disorder [ 8 , 9 ]. In the past years, infertility was considered as a shameful disease, and society and family might give individuals and couples a greater psychological burden which greatly affected the physical and mental health of infertile patients [ 10 ]. For infertile patients, first went to outpatient consultation or chose assisted reproductive technology treatment might cause anxiety [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of bibliometrics following meta-analysis, [20,21] its exponential growth in publication in recent years, [22,23] and the integration of cluster naming as a routine analysis in CiteSpace [13] and other bibliometric software (e.g., VOSviewer, [14] or Bibexcel [15] ), the use of R language in visualizing bibliometrics [24][25][26][27][28] has become more common. Drawing chord diagrams [25,29] or similar graphics using R language presents another challenge, which should be overcome immediately.…”
Section: Visualization Drawn In R Is Necessarymentioning
confidence: 99%
“…[39] The chord diagram uses 2 types of datasets: 1-mode data (within 1 entity, e.g., a countries-to-countries relationship) and 2-mode data (between entities, e.g., a countries-to-themes relationship). A variety of bibliographical studies have been conducted using 1-mode data [40][41][42][43] (e.g., author collaboration based on country of origin). However, 2-mode data have never been observed in the field of bibliometrics before.…”
Section: Classifications Of Scs Using Visualizationsmentioning
confidence: 99%